Ultra high energy cosmic rays The intersection of the Cosmic and Energy Frontiers - Coleman, Alan; Eser, Johannes; Mayotte, Eric; Sarazin, Frederic; Schröder, Frank G.; Soldin, Dennis; Venters, Tonia Moira; Aloisio, Rorberto; Alvarez-Muñiz, Jaime; Alves Batista, Rafael; Bergman, Douglas R.; Bertaina, Mario Edoardo; et al. (Astroparticle Physics, 2023)
The present white paper is submitted as part of the “Snowmass” process to help inform the long-term plans of the United States Department of Energy and the National Science Foundation for high-energy physics. It summarizes the science questions driving the Ultra-High-Energy Cosmic-Ray (UHECR) community and provides recommendations on the strategy to answer them in the next two decade